Proceedings of the 2nd Workshop on Communication Security Cryptography and Physical Layer Security (Lecture Notes in Electrical Engineering,, 2018)
This book focuses on techniques that can be applied at the physical and data-link layers of communication systems in order to secure transmissions against eavesdroppers. It discusses topics ranging from information theory-based security to coding for security and cryptography, and presents cutting-edge research and innovative findings from leading researchers. The characteristic feature of all the contributions in this book is their relevance for the practical application of security principles to a variety of widely used communication techniques, including: multiantenna systems, ultra-wide-band communication systems, power line communications, and quantum key distribution techniques. A further distinctive aspect is the attention paid to both unconditional and computational security techniques, building a bridge between two usually distinct worlds. The book gathers extended versions of contributions delivered at the Second Workshop on Communication Security, held in Paris, France, in April 2017 and affiliated with the conference EUROCRYPT 2017.